The Pharmacokinetics of Enalapril in Relation to CES1 Genotype in Healthy Danish Volunteers. Issue 6 (25th July 2017) - Stage, Claus; Jürgens, Gesche; Guski, Louise Schow; Thomsen, Ragnar; Bjerre, Ditte; Ferrero‐Miliani, Laura; Lyauk, Yassine Kamal; Rasmussen, Henrik Berg; Dalhoff, Kim
Abstract: This study investigated the influence of variations in the carboxylesterase 1 gene ( CES1) on the pharmacokinetics of enalapril. Forty‐three healthy, Danish, Caucasian volunteers representing different pre‐defined genotypes each received 10 mg of enalapril. At specified time‐points, plasma concentrations of enalapril and the active metabolite enalaprilat were measured. The volunteers were divided into six different groups according to their genetic profile of CES1 : group 1 (control group, n = 16) with two CES1 copies without non‐synonymous SNPs in the exons; group 2 (n = 5) with four copies of CES1 ; group 3 (n = 6) harbouring the G143E polymorphism; group 4 (n = 2) with three CES1 copies and increased transcriptional activity of the duplication ( CES1A2 ); group 5 (n = 4) harbouring the CES1A1c variant; and group 6 (n = 10) with three CES1 copies and the common promoter with low transcriptional activity of the duplication. The median AUC of enalaprilat in the control group was not significantly different from any of the other five groups (297 ng/ml x h in the control group versus 310, 282, 294, 344 and 306 ng/ml x h in groups 2–6, respectively). The terminal half‐life of enalaprilat was significantly longer in group 6 compared with the control group (26.7 hr versus 12.7 hr, respectively). However, this was not considered clinically relevant. In conclusion, none of the selected variations of CES1 had a clinically relevant impact on the metabolism of enalapril.